Spectrophotometric Quantitation of Tissue Culture Cell Number in Any Medium. (August 1996) - Mohler, William A.; Charlton, Carol A.; Blau, Helen M.
We have developed a spectrophotometric assay for cell number in suspensions of tissue culture cells. For each cell typetested, absorbance between 650 and 800 nm is linearly dependent upon cell density over a 50-fold range and is independent of the color or composition of the medium in which cells are suspended. A standard curve of absorbance vs. cell density is used to estimate cell number with accuracy and reproducibility superior to hemacytometer counting and with speed and ease surpassing use of a Coulter counter. Less than 5000 cells are needed for this quantitation. The same cells that are counted can be maintained live in culture after the reading is taken, thus allowing the growth of cells to be measured within individual cultures over time. The assay should be readily extended to assays of cell number directly within microplate culture wells. The spectrophotometric assay described here is of significant use in all experiments requiring rapid, accurate measurements of cell number, including determinations of cell doubling time and equal plating of parallel cultures.